Delayed imitation of lipsmacking gestures by infant rhesus macaques (Macaca mulatta). - Annika Paukner; Pier F Ferrari; Stephen J Suomi (PLoS ONE)
Human infants are capable of accurately matching facial gestures of an experimenter within a few hours after birth, a phenomenon called neonatal imitation. Recent studies have suggested that rather than being a simple reflexive-like behavior, infants exert active control over imitative responses and 'provoke' previously imitated gestures even after a delay of up to 24 h. Delayed imitation is regarded as the hallmark of a sophisticated capacity to control and flexibly engage in affective communication and has been described as an indicator of innate protoconversational readiness. However, we are not the only primates to exhibit neonatal imitation, and delayed imitation abilities may not be uniquely human. Here we report that 1-week-old infant rhesus macaques (Macaca mulatta) who show immediate imitation of a lipsmacking gesture also show delayed imitation of lipsmacking, facilitated by a tendency to refrain from lipsmacking toward a still face during baseline measurements. Individual differences in delayed imitation suggest that differentially matured cortical mechanisms may be involved, allowing some newborns macaques to actively participate in communicative exchanges from birth. Macaque infants are endowed with basic social competencies of intersubjective communication that indicate cognitive and emotional commonality between humans and macaques, which may have evolved to nurture an affective mother-infant relationship in primates.